The effectiveness of ‘Student Team Achievement Divisions’ (STAD) model towards students’ achievement in the Principles of Accounting subject - Serjali, Nor Azzatul Akmarisha; Abdul Halim, Hazianti (International Business Education Journal, 2020)
The purpose of this study was to determine the effectiveness of the STAD model towards students’ achievement in the Principles of Accounting subject, specifically in the Ledger topics. This study also evaluated students' understanding, motivation, attitude and interest in learning Principles of Accounting after using the STAD model. A quantitative approach with a quasi-experimental design was used. The sample selection involved Form 4 students from the social science stream comprising 30 students in the treatment group and 30 students in the control group. The research instruments used were pre-test, post-test and a survey questionnaire. The data was analyzed using the descriptive and inferential analysis. The descriptive analysis was used to describe students' perceptions of learning Principles of Accounting after using the STAD model. The inferential analysis involved analysis such as independent sample t-tests, paired sample t-tests and Pearson correlation analysis to explain the differences and relationships between the variables of the study. The findings showed that there was a significant difference between the treatment group and the control group in the post-test whereby the treatment group showed a significant and higher improvement (mean score= 18.267) compared to the control group (mean score= 15.133). The Pearson correlation analysis also showed a strong relationship (r= 0.745) between the STAD model and student achievement in post-test analysis. The results of the students' perceptions of Principles of Accounting after using the STAD model showed that their levels of understanding and motivation were high. The findings of this study showed that the STAD model improved students' achievement, understanding and motivation in Principles of Accounting subject. The implications of this study indicated that the STAD model could enhance the learning effectiveness of Principles of Accounting.